The effect of occupational exposure to ergonomic risk factors on osteoarthritis of hip or knee and selected other musculoskeletal diseases: A systematic review and meta-analysis from the WHO/ILO Joint Estimates of the Work-related Burden of Disease and Injury. (May 2021) - Hulshof, Carel T.J.; Pega, Frank; Neupane, Subas; Colosio, Claudio; Daams, Joost G.; Kc, Prakash; Kuijer, Paul P.F.M.; Mandic-Rajcevic, Stefan; Masci, Federica; van der Molen, Henk F.; Nygård, Clas-Håkan; Oakman, Jodi; et al.
Highlights: WHO and ILO develop joint estimates of work-related burden of disease and injury. Systematic review on osteoarthritis (OA) and musculoskeletal disorders (MSD). 8 studies (in total 378, 729 subjects) in 6 countries met the inclusion criteria. Exposure to ergonomic risk factors increases the risk of MSD and OA of knee or hip. Body of evidence is judged as 'limited evidence of harmfulness'. Abstract: Background: The World Health Organization (WHO) and the International Labour Organization (ILO) are developing joint estimates of the work-related burden of disease and injury (WHO/ILO Joint Estimates), with contributions from a large network of experts. Evidence from mechanistic data suggests that occupational exposure to ergonomic risk factors may cause selected other musculoskeletal diseases, other than back or neck pain (MSD) or osteoarthritis of hip or knee (OA). In this paper, we present a systematic review and meta-analysis of parameters for estimating the number of disability-adjusted life years from MSD or OA that are attributable to occupational exposure to ergonomic risk factors, for the development of the WHO/ILO Joint Estimates. Objectives: We aimed to systematically review and meta-analyse estimates of the effect of occupational exposure to ergonomic risk factors (force exertion, demanding posture, repetitiveness, hand-arm vibration, lifting, kneeling and/or squatting, and climbing) on MSD and OA (two outcomes: prevalence and incidence). Data sources: We developed and published a protocol, applying the Navigation Guide as an organizing systematic review framework where feasible. We searched electronic academic databases for potentially relevant records from published and unpublished studies, including the International Trials Register, Ovid Medline, EMBASE, and CISDOC. We also searched electronic grey literature databases, Internet search engines and organizational websites; hand-searched reference list of previous systematic reviews and included study records; and consulted additional experts. Study eligibility and criteria: We included working-age (≥15 years) workers in the formal and informal economy in any WHO and/or ILO Member State but excluded children (<15 years) and unpaid domestic workers. We included randomized controlled trials, cohort studies, case-control studies and other non-randomized intervention studies with an estimate of the effect of occupational exposure to ergonomic risk factors (any exposure to force exertion, demanding posture, repetitiveness, hand-arm vibration, lifting, kneeling and/or squatting, and climbing ≥ 2 h/day) compared with no or low exposure to the theoretical minimum risk exposure level (<2 h/day) on the prevalence or incidence of MSD or OA. Study appraisal and synthesis methods: At least two review authors independently screened titles and abstracts against the eligibility criteria at a first stage and full texts of potentially eligible records at a second stage, followed by extraction of data from qualifying studies. Missing data were requested from principal study authors. We combined odds ratios using random-effect meta-analysis. Two or more review authors assessed the risk of bias and the quality of evidence, using Navigation Guide tools adapted to this project. Results: In total eight studies (4 cohort studies and 4 case control studies) met the inclusion criteria, comprising a total of 2, 378, 729 participants (1, 157, 943 females and 1, 220, 786 males) in 6 countries in 3 WHO regions (Europe, Eastern Mediterranean and Western Pacific). The exposure was measured using self-reports in most studies and with a job exposure matrix in one study and outcome was generally assessed with physician diagnostic records or administrative health data. Across included studies, risk of bias was generally moderate. Compared with no or low exposure (<2 h per day), any occupational exposure to ergonomic risk factors increased the risk of acquiring MSD (odds ratio (OR) 1.76, 95% confidence interval [CI] 1.14 to 2.72, 4 studies, 2, 376, 592 participants, I 2 70%); and increased the risk of acquiring OA of knee or hip (OR 2.20, 95% CI 1.42 to 3.40, 3 studies, 1, 354 participants, I 2 13%); Subgroup analysis for MSD found evidence for differences by sex, but indicated a difference in study type, where OR was higher among study participants in a case control study compared to study participants in cohort studies. Conclusions: Overall, for both outcomes, the main body of evidence was assessed as being of low quality. Occupational exposure to ergonomic risk factors increased the risk of acquiring MSD and of acquiring OA of knee or hip. We judged the body of human evidence on the relationship between exposure to occupational ergonomic factors and MSD as "limited evidence of harmfulness" and the relationship between exposure to occupational ergonomic factors and OA also as "limited evidence of harmfulness". These relative risks might perhaps be suitable as input data for WHO/ILO modelling of work-related burden of disease and injury. Protocol identifier: https://doi.org/10.1016/j.envint.2018.09.053 PROSPERO registration number: CRD42018102631